The World Bank, IDA and IFC Policies and Operations (Washington D.C.: World Bank/IDA/IFC, 1969)
The book examines the activities of the World Bank and its two affiliates, the International Development Association and the International Finance Corporation in the promotion of economic development among the 110 members.
osc 9/8/17
Loans
Keywords: World Bank